Power and resistance in schools: Implementing institutional change to promote health equity for sexual and gender minority youth - Shattuck, Daniel; Richard, Bonnie O.; Jaramillo, Elise Trott; Byrd, Evelyn; Willging, Cathleen E. (Frontiers in Health Services, 2022)
Introduction Schools in the United States are hierarchical institutions that actively (re)produce the power relations of the wider social world, including those associated with heteronormativity. Structural stigma, informed by heteronormativity and perpetuated through schools, contributes to the production of academic and health disparities among youth who are lesbian, gay, bisexual, transgender, queer, or of other gender and sexual identities (LGBTQ+). We draw upon 5 years of qualitative data from a cluster randomized controlled trial conducted in New Mexico that used implementation science frameworks to promote the uptake and sustainment of evidence-informed practices (EIPs) to examine how power operates to hinder or promote the ability of school staff to change school environments, disrupt structural stigma, and increase safety and support for LGBTQ+ youth. Methods Data sources included annual individual and small group qualitative interviews with school professionals (e.g., administrators, school nurses, teachers, and other staff), several of whom took part in Implementation Resource Teams (IRTs) charged with applying the EIPs. Other data sources included bi-weekly periodic reflections with implementation coaches and technical assistance experts. Data were recorded, transcribed, and analyzed using deductive and inductive coding techniques. Results The IRTs experienced variable success in implementing EIPs. Their efforts were influenced by: (1) constraining school characteristics, including staff turnover and resource scarcity; (2) community-based opposition to change and concerns about community backlash; (3) the presence or absence of supportive school leadership; and (4) variations in school, district, and state policies affecting LGBTQ+ students and attitudes about their importance. Findings illustrate how diverse power structures operated in and across outer and inner contexts to bound, shift, amplify, and otherwise shape how new practices were received and implemented. Conclusion Findings indicate that the efforts of IRTs were often a form of resistant power that operated within and against school hierarchies to leverage epistemic, discursive, and material power toward implementation. To improve health equity, implementation scientists must attend to the multiple real and perceived power structures that shape implementation environments and influence organizational readiness and individual motivation. Implementers must also work to leverage resistant power to counter the institutional structures and social norms that perpetuate inequities, like heteronormativity and structural stigma.